Relationship between behaviors associated with Attention deficit hyperactivity disorder (ADHD) and the upbringing styles from the appreciation of adults - Molina Del Rio, Jahaziel (2016)
The present study proposes to characterize the relationship between upbringing styles and ADHD related behaviors. This involved the participation of 46 parents of children belonging to the elementary school Juan A. Mateos, who were asked to respond to the Adaptation of the Parenting Questionnaire, and the survey of diagnostic criteria for Attention deficit disorder and hyperactivity. We performed an X2 test of the data obtained for the variables of upbringing style and suspected ADHD referred by adults (parents and teachers), suggesting a relationship between authoritarian parenting style and non-suspected ADHD by parents, also showing according to the appreciation of teachers a relationship between permissive parenting style and suspected ADHD.